Effect of intermittent inspiratory leaks on measurement of lung clearance index using nitrogen and sulfur hexafluoride. Issue 4 (19th October 2018) - Whitfield, Carl A.; Jensen, Oliver E.; Horsley, Alex
Leaks during inert gas washout are a major potential source of measurement error in multiple-breath washout (MBW) testing. Visible leaks require exclusion of the whole test repeat [1], whilst undetected leaks may lead to significant errors in estimation of washout indices such as lung clearance index (LCI) and functional residual capacity (FRC) [2]. A recent study attempted to assess the impact on FRC and LCI of leaks of varying magnitude and type using clinically generated data modified to replicate the impact of leaks [2]. This approach is limited by the source data and the assumption that all leaked gas is mixed evenly. The authors, however, showed that the impact of expiratory leaks during nitrogen (N2 ) MBW was dependent on their size, duration and the point at which they occurred in washout. In contrast, inspiratory leaks invariably led to substantial increases in both FRC and LCI as a result of the introduction of fresh tracer gas into the lungs (room air, containing 80% N2 ). The size of leaks being modelled, however, was substantial (10–50% of tidal volume) and at a level that it is hoped should be visible during testing. Smaller leaks may well be common but may not be visible, yet in the case of N2 washout, may still cause significant inaccuracy in washout indices. Given the recognised differences in sulfur hexafluoride (SF6 ) and N2 washouts, we were interested to discover what level of inspiratory leak would have negligible impact on LCIN2 and to compare this to LCISF6, where small leaks of inspired air do not introduce new tracer gas into the lungs. In order to do this, we have used a recently described mathematical lung model of wash-in–washout that allows a more detailed interpretation of leak impact in situations of minimal leak. Even small air leaks can have a significant impact on LCI measured using N2 . This is particularly the case for leaks that occur towards the end of washout. In contrast, leaks generally have a much smaller impact on LCI measured by SF6 . http://ow.ly/az7b30lG5Ku